If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying t + -4 = 32 Reorder the terms: -4 + t = 32 Solving -4 + t = 32 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + t = 32 + 4 Combine like terms: -4 + 4 = 0 0 + t = 32 + 4 t = 32 + 4 Combine like terms: 32 + 4 = 36 t = 36 Simplifying t = 36
| 5b^2-37b+42=0 | | -t+9=2t-15 | | 4m+7=10m+7 | | 1050+800+6x=850+400+9x | | -5x^2+x-18=0 | | x+6y=25 | | -2-5=4x+2 | | 3(2x+9)=4(x+11) | | -8u-19=-5u+11 | | t(4)=32 | | 2v-15=7v-5 | | 2=1.16x+x | | -7v-4=4v+18 | | 2z+20=5z-7 | | e^3=5-2x | | 5w-7=9w+9 | | 3(4x+4)+(-50x)-9(-8-x)= | | 2w-14=7w+1 | | 5x2/3-3x1/3 | | 2w+3=4w+2 | | 1/2(x-4)=2(x+2) | | -9v-4=-v-12 | | 2x^2-19+9=0 | | 4t-18=-t-13 | | 4t-18=-3-13 | | 4b+5=19 | | 9v+19=7v+5 | | 5m+m=132 | | 4z-3=-3z-3 | | x-8.6=3.2 | | 10-7lnx=-4 | | r-7/9=20/9 |